2020
DOI: 10.1097/pas.0000000000001442
|View full text |Cite
|
Sign up to set email alerts
|

Embryonal Rhabdomyosarcoma of the Ovary and Fallopian Tube

Abstract: DICER1 mutations (somatic or germline) are associated with a variety of uncommon neoplasms including cervical and genitourinary embryonal rhabdomyosarcoma (ERMS). We report a primary ovarian and 2 primary fallopian tube ERMS occurring in 60-, 13-, and 14-year-olds, respectively. The 3 neoplasms exhibited a similar morphologic appearance being polypoid and containing edematous hypocellular areas and hypercellular foci composed of small cells with scant cytoplasm exhibiting rhabdomyoblastic differentiation (desm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…In contrast, most cases of molecularly analyzed ERMS of the uterine corpus and cervix harbor DICER1 mutations [ 7 ]. In addition, few cases of ERMS arising in the broad ligament, the ovary, and the fallopian tube are also DICER1 mutation-positive [ 18 , 20 ]. In combination with published evidence, our results suggest that ERMS of the inner female genital tract—maybe with the exception of most tumors arising in the vagina—are associated with DICER1 mutations, in contrast to other ERMS arising in the urinary tract which is usually DICER1 -wt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, most cases of molecularly analyzed ERMS of the uterine corpus and cervix harbor DICER1 mutations [ 7 ]. In addition, few cases of ERMS arising in the broad ligament, the ovary, and the fallopian tube are also DICER1 mutation-positive [ 18 , 20 ]. In combination with published evidence, our results suggest that ERMS of the inner female genital tract—maybe with the exception of most tumors arising in the vagina—are associated with DICER1 mutations, in contrast to other ERMS arising in the urinary tract which is usually DICER1 -wt.…”
Section: Discussionmentioning
confidence: 99%
“…While clinical information on DICER1-associated ERMS has rarely been published to date, potentially aggressive behavior of these tumors is exemplified by one of our patients who died of disease 3 years after initial diagnosis. Further, McCluggage et al recently reported a DICER1 -mut ERMS of the ovary, which relapsed only 3 months after surgery [ 20 ]. Given the above, further investigations of the clinical behavior of DICER1 -mut ERMS are clearly needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, many of these DICER1associated neoplasms have some site dependent morphological resemblance to the developmental stages in organogenesis, resulting into a teratoid or blastomatous appearance in many of them. Foci of cartilage are another common feature of several DICER1-associated lesions and represent a strong histological clue to suspicion of the disorder [29]. Indeed, the presence of cartilage in these DICER1-related teratoid thyroid neoplasms might have enhanced misinterpretation of malignant thyroid teratoma as being related to genuine germ cell tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that DICER1-associated malignancies, especially with blastomaoid components, show SALL4 expression. 10,11 However, owing to the limited data available, this interpretation needs further supportive evidence.…”
Section: Discussionmentioning
confidence: 99%